Resolution of Q Fever-Associated Cryoglobulinemia With Anti-CD20 Monoclonal Antibody Treatment - Kellie L. Hawkins MD, MPH; Edward N. Janoff MD; Robert W. Janson MD (SAGE Publishing, 2017)
Immunologic phenomena can complicate chronic infections with Coxiella burnetii (Q fever), including immune complex deposition causing vasculitis, neuropathy, and glomerulonephritis. We describe the case of a man with Q fever endocarditis, mixed cryoglobulinemia, and life-threatening vasculitis driven by immune complex deposition who was successfully treated with B cell depleting therapy (rituximab).